Key Leadership Traits in Madrasah Principals: Decision-Making, Motivation, Communication, and Management Skills - Muammar Asykur; Sitti Muthmainnah (Journal of Educational Management Research, 2024)
This study analyzes the leadership traits of school principals in Madrasah, focusing on their decision-making abilities, motivational skills, communication proficiency, and capability to manage subordinates. The research utilizes a qualitative descriptive methodology. Data were collected through interviews, observations, and documentation, with informants selected using purposive sampling to ensure relevance and accuracy. The findings reveal that effective leadership in Madrasahs is characterized by the principal's strong decision-making abilities, the capacity to motivate staff, excellent communication skills, and effective control over subordinates. These traits collectively contribute to the school's overall success and smooth operation. The study underscores the importance of these leadership traits in educational settings, providing valuable insights for developing training and professional development programs for school leaders. Enhancing these skills can lead to improved school management and better educational outcomes.